2D:4D RATIO VARIATION, BMI AND PULSE RATE AMONG SUBJECTS WITH NORMAL AND ABNORMAL THYROID FUNCTION - Dr. Sona Truman; Dr. Anand R.L. (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background The anthropometric measurement, second to fourth digit ratio (2D:4D) is an indication of prenatal testosterone exposure and not influenced by adult hormone levels. Polymorphism of the androgen receptor gene is responsible for individual difference in 2D:4D ratio. The androgen receptors polymorphism and thyroid functions have rarely been compared even though they belong to the same superfamily of receptors. Objective To study the relation between 2D:4D ratio, thyroid dysfunction and other metabolic markers like BMI and pulse rate. Methods A descriptive cross-sectional study design was conducted in the out-patient General Medicine department, of a tertiary care hospital of central Kerala. This research was conducted after obtaining ethical clearance from the institutional ethical committee. The 2D:4D ration was calculated for each subject. The pulse rate was recorded for each subject. The BMI was calculated for each subject. Results There is no significant change in 2D:4D ratio in the hypothyroid subjects (P = 0.944). There is no significant change in 2D:4D ratio in the hyperthyroid subjects (P = 0.987). There was no significant correlation between BMI and 2D:4D ratio. There is no significant change in pulse rate in the hypothyroid subjects (P = 0.657). There is significant change in pulse rate in the hyperthyroid subjects (P = <0.001). Conclusions This study did not show significant changes in 2D:4D ratio in subjects with abnormal thyroid function. There was significant increase in P value in BMI calculations in hypothyroid subjects. There was significant decrease in P value in BMI calculations in hyperthyroid subjects. There was significant increase in P value in pulse rate in hyperthyroid subjects. These are comparable to values obtained in similar studies.